It is given that
. prove
![= > ({a \: cosB - b \: sinB}) = \sqrt{ {a}^{2} + {b}^{2} - {c}^{2}.} = > ({a \: cosB - b \: sinB}) = \sqrt{ {a}^{2} + {b}^{2} - {c}^{2}.}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%28%7Ba+%5C%3A+cosB+-+b+%5C%3A+sinB%7D%29+%3D+%5Csqrt%7B+%7Ba%7D%5E%7B2%7D+%2B+%7Bb%7D%5E%7B2%7D+-+%7Bc%7D%5E%7B2%7D.%7D+)
Answers
Answered by
0
Solution:
It is given that
Squaring both sides,
Hence, it is proved.
Answered by
2
☯.. Refer the attachment.. ☯
☯.. Hope It Helps You.. ☯
Attachments:
![](https://hi-static.z-dn.net/files/d53/6275262734b9d354b53ddd68bd5cb7db.jpg)
Similar questions
Hindi,
7 months ago
Physics,
1 year ago
Math,
1 year ago
World Languages,
1 year ago
History,
1 year ago